To simplify the expression step-by-step, we will follow the order of operations (PEMDAS/BODMAS).
The expression is structured as follows:
\[ \frac{-1 + (-3)^3}{8^1 + (-1)} \div \frac{10 + (-8)}{4 + (-5)} \]
Step 1: Calculate the individual components
Numerator of the first fraction
- Calculate \((-3)^3\): \[ (-3)^3 = -27 \]
- Now evaluate the entire numerator: \[ -1 + (-27) = -1 - 27 = -28 \]
Denominator of the first fraction
- Calculate \(8^1 + (-1)\): \[ 8^1 = 8 \] \[ 8 + (-1) = 8 - 1 = 7 \]
So the first fraction becomes: \[ \frac{-28}{7} = -4 \]
Step 2: Calculate the second fraction
Numerator of the second fraction
- Calculate \(10 + (-8)\): \[ 10 - 8 = 2 \]
Denominator of the second fraction
- Calculate \(4 + (-5)\): \[ 4 - 5 = -1 \]
So the second fraction becomes: \[ \frac{2}{-1} = -2 \]
Step 3: Now we have
The overall expression now simplifies to: \[ -4 \div (-2) \]
Step 4: Perform the division
- Calculate \(-4 \div (-2)\): \[ -4 \div -2 = 2 \]
Final Result
The simplified expression is: \[ \boxed{2} \]